STUDI EKSPERIMEN LIMA MACAM WARNA GLASIR PADA LIMA KARAKTER TANAH LIAT - Yustana, Prima (Institut Seni Indoensia Surakarta, 2010)
This study attempts to solve common problems faced in ceramic finishing. Finishing ceramic objects is different from resolving other matters. Glaze is a type of glass coating that is applied to coat the ceramic object. This is an interesting layer to be studied because the success of glaze applications in ceramics is influenced by many factors. Glaze applications on ceramic objects have a very high level of difficulty. The difficulty is seen in glaze formulas, application techniques, firing temperature, shrinkage of dry matter and the successful achievement of color after glazing the combustion process. This research is to determine whether the clay character influence on the success rate of the color will appear. The research method uses the experimental method. This method is considered more appropriate to determine the level of success of an experiment relating to the material containing chemical elements. The research is done in the studio ceramics P4TK Art and Culture of Yogyakarta.The clay used is a type of stoneware clay which has five classes of characters. They are as follows: 1. Pacitan soil, wet soil that has a reddish color, 2. Singkawang soil, wet soil that has a whitish colour, 3.Sukabumi has a brightly colored ground and wet floor is beige, with 4. Sukabumi, the dark ground, wet soil that has a dark brown color, 5. Bojonegoro soil, wet soil that has a light brown color. The five characters color glazing that shall be applied on the surface of clay are: 1. young Greens, 2. Pink, and 3. Greenish blue, 4. Brown 5. Dark blue.The character of clay has relatively large contribution to the emergence of color glaze in accordance to the purpose or the plan, especially when using a formula based on the glossy glaze. Glaze formula will tend to be stable when there is a combination of stain with a glade oxide. Stable formula can also be found on the matched glaze because its glaze was close or not transparent. Coloring oxides are very sensitive to the character of soil. temperature change is cobalt and fee, experiment that required in advance when the formula contains two types of oxide glaze. Burning with the reduction or oxidation also will give effect to the glaze colors that will appear. Keywords: experiment, five colors glaze, five characters clay